COMPARATIVE HISTOLOGICAL STUDY OF GILLS OF TWO SPECIES IN FRESH WATER )CYPRINUS CARPIO) AND SEA WATER FISH (OTOLITHES RUBER) OF IRAQ - Alaa A. Al-Sawad; Majdi F. Majeed; Alia M. Khuder (Basrah Journal of Veterinary Research)
In present study investigated of the histological structure of the gills of two fish species: Cyprinus carpio and Otolithes rubber which represented fresh water and seawater fish respectively. A total 20 specimens of freshwater fish (Cyprinus carpio) collected from Shatt-Al-Arab and 20 specimens of seawater fish(Otolithes ruber) were collected from Arabian Gulfs. The histological examination of gill samples showed that the seawater samples had a larger number of the chloride and pavement cells, compare with C. carpio. Also the gill raker of the O. rubber was appeared a cartilage and osseous tissue in the external side, while fibrous connective tissue, skeletal muscle layer and large amounts of adipose tissue was noticed in internal side, while the rake gills of the freshwater fish C. carpio was showed lake of the bone and skeletal muscle as well as adipose tissue.